Historický vývoj posturálnych stratégií a prehltacích manévrov v behaviorálnej liečbe orofaryngeálnej dysfágie - Adzimová, Silvia; Speyer R; Tedla, Miroslav (Česká a slovenská neurologie a neurochirurgie, 2022)
Dysphagia or swallowing disorder is a highly prevalent, yet underdiagnosed condition, which has potential severe medical consequences. The treatment of dysphagia can be medical-surgical, medical-nonsurgical and behavioral. Behavioral treatment is mostly delivered by a clinical speech and language pathologist within the multidisciplinary team. The aim of our work is to review the historical scope of the most commonly used postural strategies and swallowing maneuvers described along with their rationale and effects of interventions in the behavioral treatment of oropharyngeal dysphagia.
Keywords: terapie cvičením; Rehabilitation; poruchy polykání; lidé; Humans; rehabilitace; Deglutition Disorders; Exercise Therapy